ANALISIS RESEPSI PENGGUNA SNACK VIDEO TERHADAP APLIKASI SNACK VIDEO PENGHASIL UANG - Prameswari Widya Ningrum; Poppy Febriana; Totok Wahyu Abadi (Jurusan Ilmu Komunikasi Universitas Andalas, 2022)
We are currently in the modern era, where the era is all sophisticated, sophisticated and easy. New media or new media are media whose development and progress are accompanied by sophisticated technology. Currently, there are many social media applications that are used by many people. One of them is a social media application, namely video snacks. is a short video-based social media application with various features and video content. In addition to providing these music videos, this application can also give free money to its users. The purpose of this study was to determine user acceptance of video snack applications for video snacks. This study uses a qualitative method, with the reception analysis method, the number of informants using 5 people, with data collection techniques through interviews. The result of this research is the acceptance of 3 informants from 5 informants tend to be in a dominant hegemonic position and 2 people are in a negotiating position.